Embriogênese somática em mamoeiro seleção THB - Detoni, Jamile Lenhaus (2013)
This work aimed to assess the somatic embryogenesis in juvenile explants from the papaya tree selection THB. Apex stems and cotyledonary leaves inoculated by induction medium (IM): MS salts, sucrose (30 g L-1), myo-inositol (100 mg L-1), Phytagel® (2.8 g L-1) and concentrations of 2,4-D (6; 9; 12; 15 and 18 µM) or 4-CPA (19; 22; 25; 28 and 31 µM). After 50 days, the embryogenic calluses were transferred to the maturation medium (MM): MS without growth regulator; ABA (0.5 µM); ABA (0.5 µM) + CA (15 g L-1 ); ABA (0.5 µM) + CA (30 g L-1 ); ABA (0.5 µM) + PEG (60 g L1 ) for 30 days. The data were submitted to analysis of variance by the F test and the averages compared by the Tukey test in level of 5% and analysis of regression. In IM, for both auxins, the responses were superior than when cotyledonary leaves were used, except the callogenesis. For the somatic embryo types, embryos in premature phase prevailed in both auxins, like globular and heart-shaped ones. For the 2,4-D, it was not possible to establish a great concentration for the response, but with the 4-CPA all the variables had their maximum level close to 25 µM. In this concentration, it was possible to obtain 91.67% of embryogenic calluses in cotyledonary leaves. For histological analysis of cotyledonary leaves, it was possible to identify the somatic embryos formation from parenchyme cells, prevailing the indirect form, but not synchronized. The occurrence of secondary somatic embryogenesis and the formation of abnormal embryos were also identified. For the maturation process, in the composition of the medium in which was detected a larger occurrence of somatic embryos (70 ES calo-1 ), as well as a lower percentage of geminated ES (4%), there was ABA (0.5 µM) + CA (15 g L-1 ). Therefore, for the somatic embryogenesis of the papaya tree selection THB, it is recommended the induction of cotyledonary leaves in 4-CPA (25 µM), being the maturation in an medium with ABA (0.5 µM) + CA (15 g L-1 ).